Development status of young new farmers from the perspective of vocational ability: A research analysis based on 21 cities in Guangdong Province - Tao Luo; Qingpeng Huang; Jingyan Mai (PLoS ONE, 2026)
Professional competence refers to the comprehensive qualities that an individual needs to possess in order to continuously develop and achieve excellent performance in their professional activities. As more and more young people enter the agricultural sector, the professional competence of young new farmers not only affects their personal growth but also directly influences the transformation of agriculture and the development of rural areas. Based on data obtained from in-depth interviews and questionnaires, this paper examines the career development of young new farmers from three aspects: entering agriculture, rooting in agriculture, and developing agriculture, with a focus on their identity formation, influencing factors, and development paths. Research shows that the professional abilities of young new farmers mainly include three levels: professional skills, general abilities, and core literacy. The improvement of abilities at different levels requires corresponding cultivation methods. The research conclusions can provide references for the training of young agricultural talents and the improvement of rural talent revitalization policies.